PERAN ARSIPARIS DALAM ADVOKASI ARSIP FILM: STUDI KASUS SINEMATEK INDONESIA - Author, Nailul; Susetyo, Tamara Adriani; Putra, Riyan Adi (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
(Objectives) The Role of Archivists in Film Archive Advocacy Case Study of Sinematek Indonesia, This article discusses the role of archivists in film archive advocacy, with a case study at Sinematek Indonesia. This article aims to look at the role played by archivists at Sinematek to advocate for the archives owned by Sinematek Indonesia. (Method) This research uses a qualitative method with a case study approach, with primary data sources from interviews and secondary sources from observation and related literature. The research stages include data reduction, data presentation, and conclusion drawing, as well as data processing and data analysis techniques. (Findings) The results found that archivists at Sinematek Indonesia have an important role, where archivists build communication and relationships with members and stakeholders of the organisation, such as establishing internal and external communication and interacting with related parties in the Ministry of Education and Culture. In this context, archivists have the responsibility to manage, maintain and protect archives and important documents that have historical, legal and administrative value. However, Sinematek Indonesia faces challenges related to limited funding and lack of public awareness on the importance of film archive preservation. This research is expected to provide a deeper understanding of the role of archivists in film archive advocacy and provide insights to support the sustainability of film archive preservation in Indonesia.